Numerical modelling of intra-wave sediment transport on sandy beaches using a non-hydrostatic, wave-resolving model - Mancini, Giulia; Briganti, Riccardo; McCall, Robert; Dodd, Nicholas; Zhu, Fangfang (2020)
The mutual feedback between the swash zone and the surf zone is known to affect large-scale morphodynamic processes such as breaker bar migration on sandy beaches. To fully resolve this feedback in a process-based manner, the morphodynamics in the swash zone and due to swash-swash interactions must be explicitly solved, e.g., by means of a wave-resolving numerical model. Currently, few existing models are able to fully resolve the complex morphodynamics in the swash zone, and none is practically applicable for engineering purposes. This work aims at improving the numerical modelling of the intra-wave sediment transport on sandy beaches in an open-source wave-resolving hydro-morphodynamic framework (e.g., non-hydrostatic XBeach). A transport equation for the intra-wave suspended sediment concentration, including an erosion and a deposition rate, is newly implemented in the model. Two laboratory experiments involving isolated waves and wave trains are simulated to analyse the performance of the model. Numerical results show overall better performance in simulating single waves rather than wave trains. For the latter, the modelling of the morphodynamic response improves in the swash zone compared with the existing sediment transport modelling approach within non-hydrostatic XBeach, while the need of including additional physical processes to better capture sediment transport and bed evolution in the surf zone is highlighted in the paper.